Reading verbal and non verbal texts: a semiotic approach - Lara, Glaucia Muniz Proença (Laboratório Editorial FCL-UNESP, 2008)
Taking the concept of text in a large sense, we intend, in this paper, to show the efficacity of the French semiotical theory – introduced by Algirdas Julien Greimas and added by the contributions of its most recent developments, mainly the ones proposed by “visual semiotics” – in reading the content plan and the expression plan of both verbal and non-verbal texts. At the same time, we try to find out the semi-symbolical relations that are established between these two plans. With such objectives in mind, we analyse a poem by Maria Quintana and a painting by Mestre Ataíde.